2019
DOI: 10.3389/fimmu.2019.00305
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Diagnosis of Axial Spondyloarthritis, Disease Activity, Prognosis, and Prediction of Response to Therapy

Abstract: There exists a major unmet need for biomarkers that can identify axial spondyloarthritis (axSpA) early after disease onset because of the availability of highly effective therapies. Several recent reports have examined the autoantibody response in patients with axSpA through the use of protein microarrays and protein-protein interactions although diagnostic performance of biomarkers identified to date has been inadequate. An example of such a biomarker is protein phosphatase magnesium-dependent 1A. Antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 57 publications
4
49
0
2
Order By: Relevance
“…Both of them play a prominent role in the metabolism of energy. It had been well reported that metabolites and proteins involved in the TCA cycle were signi cantly raised to enhance energy production, so as to compensate for insu cient energy sources caused by glycolysis under AS in ammation condition [70]. Similarity, in this study, the levels of citric acid and VCP increased in the PG-induced AS model mice group compared with the healthy control group, suggesting a boosted energy supply to compensate for the shortage of body energy.…”
Section: Mineral Absorptionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both of them play a prominent role in the metabolism of energy. It had been well reported that metabolites and proteins involved in the TCA cycle were signi cantly raised to enhance energy production, so as to compensate for insu cient energy sources caused by glycolysis under AS in ammation condition [70]. Similarity, in this study, the levels of citric acid and VCP increased in the PG-induced AS model mice group compared with the healthy control group, suggesting a boosted energy supply to compensate for the shortage of body energy.…”
Section: Mineral Absorptionsupporting
confidence: 78%
“…Some speci c gut pathogens, including the Helicobacter pylori, have been proven to trigger the release of MIF [93]. Subsequently, the production of MIF from the gut may drive the new bone formation in patients with AS via activating and mineralizing OBs, upregulating genes involved in osteogenesis, and triggering the stabilization of β-catenin, an important mediator involved in the OBspeci c Wnt/β-catenin pathway [70]. Thus, it is not surprising to detect the high concentration of MIF in patients with AS [94].…”
Section: Phenylalanine Metabolismmentioning
confidence: 99%
“…Inflammation is currently assessed by C-reactive protein (CRP), which is elevated in AS patients compared to nr-axSpA patients 8,12,13 . An increase in CRP may arise from many pathological events, such as a common cold or chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is an inflammatory rheumatic condition, involving primarily an axial skeleton and progressively leading to the sacroiliac, intervertebral and facet joint immobilization [1]. The definition of active sacroiliitis in MRI, fulfilling the ASAS (Assessment in SpondyloArthritis international Society) criteria, is bone marrow oedema visible on T2-weighted sequence sensitive for free water (e.g., STIR sequence) or bone marrow enhancement (osteitis) present on T1-weighted sequence after contrast media administration.…”
Section: Introductionmentioning
confidence: 99%